MANAGEMENT STRATEGIES IN DAIRY FARMS OF MINAS GERAIS STATE - Bassotto, Leandro Carvalho; Benedicto, Gideon Carvalho de; Putti, Fernando Ferrari [UNESP] (Univ Sul Santa Catarina-unisul, 2022)
Information is essential to analyze performance and formulate management strategies in dairy farming. In order to investigate which factors contribute to the informational development of southern Minas Gerais dairy properties and to identify business strategies that may emerge from information management in these properties, 115 southern Minas Gerais milk producers were interviewed in 2017, using Pearson's Correlation to analyze the data. Technologically less developed properties tend to have worse information management. The information contributes to the formulation of three management strategies in dairy farming (quality and storage, production and knowledge).
Keywords: dairy farming; agribusiness; milk; business strategies; Pearson's correlation